Implikasi Penerapan Sistem Pemilihan Umum Proporsional Terbuka Terhadap Akuntabilitas Anggota Legislatif - Munib, M Abdim; Safitri, Alfiani Dewi Bulan (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
Article 1 paragraph (2) of the 1945 Constitution of the Republic of Indonesia states that sovereignty is in the hands of the people and is carried out according to the Constitution. This provision affirms that Indonesia is a country that stands on the principles of democracy. One of the characteristics of a country that adheres to democracy is to hold periodic, honest and fair general elections to elect candidates for legislative members. In the implementation of general elections, it cannot be separated from the existence of an election system, which is a method that regulates citizens in electing the people's representatives. Based on Article 168 paragraph (2) of Law Number 7 of 2017 concerning Elections, the election system implemented in Indonesia is a proportional system with an open list of candidates. Based on the results of the research, the implementation of the open proportional election system has a positive impact on the accountability of legislative elections. With a proportional system with an open list of candidates, it provides a greater opportunity to build a direct relationship between voters (the people) and legislative members. Legislative members are not only obedient to political parties, but legislative members are also required to work optimally to carry out the mandate of the people (constituents) who have elected them